Gender differences in osteoporotic hip fractures in Sarawak General Hospital - Sharifah Aishah, Wan Mohamad Akbar; Ing Khieng, Tiong; Seow Lin, Chuah; Yaw Kiet, Cheong; Benjamin Sachdev, Manjit Singh; Kar Hoo, Lee; Wendy wan Hui, Lee; Cheng Lay, Teh; Jeh Kiong, Tiong; Affizal, Samsudin; Ahmad Tirmizi, Jobli (Malaysian Medical Association, 2023)
ABSTRACT Introduction: Osteoporosis and osteoporotic fracture pose a major public health problem in our ageing population, and particularly concerning is the increased morbidity and mortality associated with osteoporotic hip fractures. While overall diagnosis and treatment for osteoporosis have improved, osteoporosis in men remains underdiagnosed and undertreated. We aim to describe the difference in clinical characteristics between elderly men and women with osteoporotic hip fractures in Sarawak General Hospital. Materials and Methods: All patients diagnosed with osteoporotic hip fracture admitted to Sarawak General Hospital from June 2019 to March 2021 were recruited, and demographic data and clinical features were obtained. Results: There were 140 patients with osteoporotic hip fracture, and 40 were men (28.6%). The mean age for males was 74.1 ± 9.5 years, while the mean age for females was 77.4 ± 9.1 years (p=0.06). The types of fracture consisted of neck of femur=78, intertrochanteric=61 and subtrochanteric=1. More men were active smokers (15% vs 1%, p<0.001). There were 20 men with secondary osteoporosis (50%), while 13 women (13%) had secondary osteoporosis (p<0.001). The causes of secondary osteoporosis among the men were hypogonadism, COPD, glucocorticoid-induced osteoporosis, renal disease, androgen deprivation therapy, thyroid disorder, prostate cancer and previous gastrectomy. There were two deaths among the men and four deaths among the women during the inpatient and 3 months follow-up period. There was no statistical significance between the mortality rates between male patients (5%) and female patients (4%) (p=0.55). Conclusion: There were more females with osteoporotic hip fractures, and there were significantly more males with secondary osteoporotic hip fractures.